UPAYA PESANTREN DALAM MEWUJUDKAN KELUARGA SAKINAH (STUDI KASUS DI YAYASAN PONPES SPMAA TURI LAMONGAN) - Alfa Alfin Salvatore; Fathurrahman Alfa; Nurhasan Nurhasan (Prodi Ahwal syakhshiyyah Fakultas Agama Islam UNISMA, 2022)
The sakinah family is an important thing that must be owned by every married couple in the household, the purpose of realizing a sakinah family is to create a sense of peace and comfort in the family. The development of the times affects a person's mindset and lifestyle, especially among teenagers in the concept of marriage. For this reason, Islamic boarding schools are here to bring the concept of thinking as a result of exemplary steps in realizing a sakinah family. The author conducted research on the efforts, and implementation of Islamic boarding schools in realizing a sakinah family at the SPMAA Turi Lamongan Islamic Boarding School Foundation. In data collection techniques, researchers used interviews, observation and documentation. The results of this study focus on the efforts and implementation of Islamic boarding schools in realizing a sakinah family at the SPMAA Turi Lamongan Islamic Boarding School Foundation Kata kunci: Upaya Pesantren, Mewujudkan, Keluarga Sakinah